BmK NSP, a new sodium channel activator from Buthus martensii Karsch, promotes neurite outgrowth in primary cultured spinal cord neurons. (30th July 2020) - Zou, Xiaohan; Wang, Yujing; Yu, Yiyi; He, Jing; Zhao, Fang; Xi, Chuchu; Zhang, Chi; Cao, Zhengyu
Abstract: Scorpion venom is a rich source of bioactive compounds that affect neuronal excitability by modulating the activities of various channels/receptors. In the current study, guided by a Ca 2+ mobilization assay, we purified a new neuroactive peptide designated as BmK NSP ( Buthus martensii Karsch neurite-stimulating peptide, MW: 7064.30 Da). The primary structure of BmK NSP was determined by Edman degradation. BmK NSP concentration-dependently elevated intracellular Ca 2+ concentration ([Ca 2+ ]i ) with an EC50 value of 4.18 μM in primary cultured spinal cord neurons (SCNs). Depletion of extracellular Ca 2+ abolished BmK NSP-triggered Ca 2+ response. Moreover, we demonstrated that BmK NSP-induced Ca 2+ response was partially suppressed by the inhibitors of L-type Ca 2+ channels, Na + -Ca 2+ exchangers and NMDA receptors and was abolished by voltage-gated sodium channel (VGSC) blocker, tetrodotoxin. Whole-cell patch clamp recording demonstrated that BmK NSP delayed VGSC inactivation (EC50 = 1.10 μM) in SCNs. BmK NSP enhanced neurite outgrowth in a non-monotonic manner that peaked at 30 nM in SCNs. BmK NSP-promoted neurite outgrowth was suppressed by the inhibitors of L-type Ca 2+ channels, NMDA receptors, and VGSCs. Considered together, these data demonstrate that BmK NSP is a new α-scorpion toxin that enhances neurite outgrowth through main routes of Ca 2+ influx. Modulation of VGSC activity by α-scorpion toxin might represent a novel strategy to regulate the neurogenesis in SCNs. Graphical abstract: Image 1 Highlights: 1. A new α-scorpion toxin, BmK NSP was purified from BmK venom. 2. BmK NSP elevated intracellular Ca 2+ concentration in cultured spinal cord neurons. 3. BmK NSP promoted neurite outgrowth in cultured spinal cord neurons. 4. BmK NSP responses on both Ca 2+ and neurite were through main routes of Ca 2+ influx. 5. BmK NSP delayed inactivation of VGSCs.